EVALUASI KEBIJAKAN PROGRAM PEMUDA SARJANA PENGGERAK PEMBANGUNAN DI PERDESAAN (PSP-3) DI KOTA SAMARINDA - Kuncari Isnawati (Jurnal Administrative Reform, 2020)
The resulting research showed that the Bachelor program in rural development (PSP-3)) in Samarinda is located of Sungai Siring district, Tanah Merah district (North Samarinda) and the Sindang Sari district, Makroman District and Sungai Kapih district  (Sambutan district) has not fulfilled the criteria os effective, efficient, adequacy, similarity, accuracy as for the criteria, not all programs meet this criterion. Keywords: Evaluation, PSP-3, Policy